Nutritional assessment tools for patients with cancer: a narrative review - Wang, Peng-peng; Soh, Kim Lam; Khazaai, Huzwah; Ning, Chuan-yi; Huang, Xue-ling; Yu, Jia-xiang; Liao, Jin-lian (Huazhong University of Science and Technology, 2024)
Cancer patients are at high risk of malnutrition, which can lead to adverse health outcomes such as prolonged hospitalization, increased complications, and increased mortality. Accurate and timely nutritional assessment plays a critical role in effectively managing malnutrition in these patients. However, while many tools exist to assess malnutrition, there is no universally accepted standard. Although different tools have their own strengths and limitations, there is a lack of narrative reviews on nutritional assessment tools for cancer patients. To address this knowledge gap, we conducted a non-systematic literature search using PubMed, Embase, Web of Science, and the Cochrane Library from their inception until May 2023. A total of 90 studies met our selection criteria and were included in our narrative review. We evaluated the applications, strengths, and limitations of 4 commonly used nutritional assessment tools for cancer patients: the Subjective Global Assessment (SGA), Patient-Generated Subjective Global Assessment (PG-SGA), Mini Nutritional Assessment (MNA), and Global Leadership Initiative on Malnutrition (GLIM). Our findings revealed that malnutrition was associated with adverse health outcomes. Each of these 4 tools has its applications, strengths, and limitations. Our findings provide medical staff with a foundation for choosing the optimal tool to rapidly and accurately assess malnutrition in cancer patients. It is essential for medical staff to be familiar with these common tools to ensure effective nutritional management of cancer patients.